2020
DOI: 10.1029/2020gl088312
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Between the Vertical Evolution of Clouds and Droplet Growth Modes as Seen From FY‐4A AGRI and GPM DPR

Abstract: Based on matched scans from the FY‐4A satellite's Advanced Geostationary Radiation Imager (AGRI) and the NASA/JAXA Global Precipitation Measurement (GPM) Core Observatory's Dual‐frequency Precipitation Radar (DPR), the microphysical mechanisms of the derived vertical evolution of cloud effective radius (Re) and its correspondence with precipitation droplet growth modes are revealed in this study. The results show that there were two turning points in the Re vertical evolution, which divided the Re profile into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The DPR operates at Ku band (KuPR,13.6 GHz) and Ka band (KaPR,35.5 GHz), which can provide information on drop size distributions (DSDs) in rain and snow as well as estimations of rainfall and snowfall rates (Beauchamp et al, 2015;Hamada and Takayabu, 2016;Jackson et al, 2016). These GPM parameters are evaluated and widely adopted to study deep convective precipitation and its vertical structure (Chen et al, 2020b;Huang and Chen, 2019;Libertino et al, 2016;Liu and Liu, 2016;Pejcic et al, 2020;Zhang and Fu, 2018a;. Compared to the observation of a global rain gauge network, Libertino et al (2016) found that GPM might improve the ability of detecting extreme rainfall than TRMM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DPR operates at Ku band (KuPR,13.6 GHz) and Ka band (KaPR,35.5 GHz), which can provide information on drop size distributions (DSDs) in rain and snow as well as estimations of rainfall and snowfall rates (Beauchamp et al, 2015;Hamada and Takayabu, 2016;Jackson et al, 2016). These GPM parameters are evaluated and widely adopted to study deep convective precipitation and its vertical structure (Chen et al, 2020b;Huang and Chen, 2019;Libertino et al, 2016;Liu and Liu, 2016;Pejcic et al, 2020;Zhang and Fu, 2018a;. Compared to the observation of a global rain gauge network, Libertino et al (2016) found that GPM might improve the ability of detecting extreme rainfall than TRMM.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Chen (2019) indicated that breakup (coalescence) process is dominant with low (high) precipitation efficiency indices below the melting layer of tropical cyclone precipitation. Chen et al (2020b) analysed a disastrous rainfall-blizzard event seen from FengYun-4A AGRI and GPM DPR and revealed that main droplet growth modes were nucleation/glaciation, deposition and riming. Based on validation of the GPM DPR products with a polarimetric radar in south China, Huang et al (2021) confirmed that GPM DPR in matched scanning track can capture microphysical differences between the typhoons and squall lines, even though number concentration is underestimated for heavy rainfalls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cloud products are not only critical for weather services and nowcasting applications, but are also used in the retrieval of other key products such as "clear sky radiation (CSR)" and "atmospheric motion vector (AMV)" for numerical weather forecasting. In addition to severe weather monitoring, forecasting, and NWP services [30], these science products generated by FYGAT are also used in the research of cloud climatology and cloud and precipitation microphysics [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Fu [22] examined the microphysical processes in raindrops during each stage in the life cycle of clouds by satellite (Global Precipitation Measurement (GPM) mission). Chen et al [23] revealed the relationship between droplet growth modes and cloud particle microphysics using FY-4A satellite and GPM DPR data.…”
Section: Introductionmentioning
confidence: 99%